Pergerakan patung wayang kulit Kelantan: Perdalangan Yusoff Mamat / Nurulain Mohamad Salihuddin - Nurulain , Mohamad Salihuddin (2016)
This study is about the style of the movement of the Wayang Kulit Kelantan which were performed by a chosen dalang Yusof bin Mamat. This study focuses on the styles of the movement of puppets (patung/wayang) that presented on the white screen. Techniques and methods of the puppets movement are reviewed statue game reviewed and analyzed through observation, presentation and also interviews directly with the puppeteer. Qualitative method chosen to assist the researcher to obtain information pertaining to the title. Methods implemented are such as interviews, observations or direct involvement at the location of the show or production, also through to site presentation Wayang Kulit in Kelantan. The study is expected to help contribute information about the importance of the movement enrichment technique of Wayang Kulit Kelantan to the community and for the group of Wayang Kulit players, particularly its young leaders in the future.